BAHASA RUPA MOTIF BATIK CIAMIS MELALUI PROGRAM LINDENMAYER SYSTEMS - Ratnadewi, Ratnadewi; Pandanwangi, Ariesa; Prijono, Agus (Jurnal Bahasa Rupa, 2021)
West Java has a centre for craftsmen who have a variety of motifs drawn from their regional potential. One of them is Ciamis batik, but now with the pandemic of the Corona 19 virus, it has had a tremendous impact on the macro and micro industrial economy in the development of the batik business. More and more are stopping their business. So it is feared that Ciamis batik motifs are increasingly rare in the market. Through Turtle graphics, existing batik motifs are made in the form of vector images to be preserved by utilizing digital technology. This research has the aim to that the Ciamis batik motif can be made into a visual language through the digitalization process using the MuPAD programming language. The benefit is to document and reintroduce Ciamis Batik motifs that are almost extinct. The method used is a digitalization experiment through the Lindenmayer System. Ciamis batik samples selected motifs that have repetition in the form of a repeating pattern. Based on the research, the Ciamis batik motif can be made using the technique of arches, horizontal lines, vertical lines, and rotation. The conclusion of this research is that batik motif design can use the Lindenmayer System program as a blueprint and can be implemented on Indonesian batik.  This research contributes to the efficient documentation of batik motifs in digital form with good quality so that they can be implemented in the creative industry.